“VALVE-IN-VALVE” REPROSTHESING OF CARDIAC ARTIFICIAL VALVES - R. Yu. Klyshnikov; E. A. Ovcharenko; Yu. A. Kudryavtseva; L. S. Barbarash (Российский кардиологический журнал, 2016)
Recently, the number of cardiac surgery in the world and particularly in Russia is raising, especially with utilization of biological prostheses; it is related to average population ageing too. Main disadvantage of such devices is restricted time period of work due to degrading of biomaterials, which demands additional surgery in longterm period (5-10 years). The technology of alternative reimplantation of bioprosthesis by method “prosthesis-into-prosthesis” using transcatheter low invasive devices is the most promising solution for the mortality risk reduction from operations on replacement of failing prosthesis. Current review includes an analysis of clinical results of application of that methodology for correction of acquired defects of aortic, mitral, tricuspid valves, and pulmonary artery valve. The results that are described, witness increasing interest of the world society in methodic as “prosthesis-into-prosthesis”, presenting via attempts for systematization and structuring of the interventions results. However complications that occur, risk and procedure restrictions significantly slow wider spread of the method application.